2015
DOI: 10.1038/srep14746
|View full text |Cite
|
Sign up to set email alerts
|

A strategy to discover decoy chemokine ligands with an anti-inflammatory activity

Abstract: Excessive signaling by chemokines has been associated with chronic inflammation or cancer, thus attracting substantial attention as promising therapeutic targets. Inspired by chemokine-clearing molecules shaped by pathogens to escape the immune system, we designed a generic screening assay to discover chemokine neutralizing molecules (neutraligands) and unambiguously distinguish them from molecules that block the receptor (receptor antagonists). This assay, called TRIC-r, combines time-resolved intracellular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 52 publications
(64 reference statements)
0
39
0
Order By: Relevance
“…To our knowledge the importance of B cell expressed CCR4 in the human germinal center response has however not previously been investigated. These findings have important clinical implications given that high affinity neutraligands have been developed for CCL22 and CCL17, and these inhibit both the chemokine-induced intracellular calcium responses and CCR4 endocytosis in vitro , and inflammation in vivo in a murine model of asthma58. Of relevance to atopic dermatitis, the synthetic molecule 5,6-dihydroergosteol-glucoside (DHE-Glc) has also been shown to suppress TNF-α/IFN-γ-induced expression of CCL17 and CCL22 in the human keratinocyte cell line HaCaT, and attenuate levels of CCL22, CCL17 and IgE in a mouse model of atopic dermatitis as well as improve skin inflammatory symptoms59.…”
Section: Discussionmentioning
confidence: 92%
“…To our knowledge the importance of B cell expressed CCR4 in the human germinal center response has however not previously been investigated. These findings have important clinical implications given that high affinity neutraligands have been developed for CCL22 and CCL17, and these inhibit both the chemokine-induced intracellular calcium responses and CCR4 endocytosis in vitro , and inflammation in vivo in a murine model of asthma58. Of relevance to atopic dermatitis, the synthetic molecule 5,6-dihydroergosteol-glucoside (DHE-Glc) has also been shown to suppress TNF-α/IFN-γ-induced expression of CCL17 and CCL22 in the human keratinocyte cell line HaCaT, and attenuate levels of CCL22, CCL17 and IgE in a mouse model of atopic dermatitis as well as improve skin inflammatory symptoms59.…”
Section: Discussionmentioning
confidence: 92%
“…In vitro experiments have indicated that these neutraligands can inhibit CCL17- or CCL22-induced intracellular calcium responses, CCR4 endocytosis, and human T cell migration. Furthermore, in an in vivo experiment, neutraligands inhibited inflammation in a murine model of asthma [ 114 ].…”
Section: Therapeutic Targeting Of Ccl17/ccl22 and Ccr4mentioning
confidence: 99%
“…“Treat-to-target” strategies hope to avoid the systemic side effects of steroids. It is also known that pathogens manipulate the human immune system, such as encoding for CKs, CKRs, soluble proteins, or extracellular matrix-mimicking components ( 177 ). All of these decoy proteins prevent CK binding to GAGs and extracellular CK gradients that attract circulating immune cells or CK binding to its cognate receptor ( 177 ).…”
Section: Targeting Cks or Other Cytokinesmentioning
confidence: 99%